Bicornuate uterus is an independent risk factor for cervical os insufficiency: A retrospective population based cohort study. (17th November 2017) - Mastrolia, Salvatore Andrea; Baumfeld, Yael; Hershkovitz, Reli; Loverro, Giuseppe; Di Naro, Edoardo; Yohai, David; Schwarzman, Polina; Weintraub, Adi Yehuda
Abstract: Introduction: The purpose of our study was to explore maternal and fetal outcomes in the second and third trimester in women with bicornuate uterus. Methods: A total of 280, 106 pregnancies met the inclusion criteria and were divided in two study groups: (1) pregnancies in women with bicornuate uterus ( n  = 444); and (2) controls ( n  = 279, 662). The diagnosis of bicornuate uterus was performed in all patients during the workup for infertility or recurrent pregnancy loss, during pregnancy, or at the time of cesarean delivery. Multivariate logistic regression models were performed in order to assess the risk factors for cervical insufficiency in women with bicornuate uterus. Results: The rate of women with a bicornuate uterus in our population was 0.15%. Women with bicornuate uterus had lower parity (2.93 ± 1.90 vs. 3.42 ± 2.51, p  < 0.001) and a higher rate of previous cesarean deliveries (54.1% vs. 12.3%, p  < 0.001). In addition, these patients were more prone to conceive with assisted reproductive techniques (5.6% vs. 1.9%, p  < 0.001) and had a significantly higher rate of recurrent abortions (12.4% vs. 5.1%, p  < 0.001) compared to controls. Conclusions: Bicornuate uterus is an independent risk factor for cervical os insufficiency. This is an important finding due to the burden of the risk for midtrimester periviable birth associated with cervical incompetence.